Financing Firms in Hibernation during the COVID-19 Pandemic - Didier, Tatiana; Huneeus, Federico; Larrain, Mauricio; Schmukler, Sergio L. (World Bank, Washington, DC, 2020)
The coronavirus (COVID-19) pandemic has halted economic activity worldwide, hurting firms and pushing them toward bankruptcy. This paper provides a unified framework to organize the policy debate related to firm financing during the downturn, centered along four main points. First, the economic crisis triggered by the spread of the virus is radically different from past crises, with important consequences for optimal policy responses. Second, to avoid inefficient bankruptcies and long-term detrimental effects, it is important to preserve firms' relationships with key stakeholders, like workers, suppliers, customers, and creditors. Third, firms can benefit from "hibernating," using the minimum bare cash necessary to withstand the pandemic, while using credit to remain alive until the crisis subdues. Fourth, the existing legal and regulatory infrastructure is ill-equipped to deal with an exogenous systemic shock such as this pandemic. Financial sector policies can help increase the provision of credit, while posing difficult choices and trade-offs.